Intercultural Hermeneutics. Vol. 1 of Intercultural Theology - Muck, Terry C. (International bulletin of mission research, 2017)
The global Christian church is culturally diverseand getting more so every day. As a church, we need to faithfully embrace that diversity and then commit ourselves to developing a way of understanding and loving one another, in spite of cultural difference and misunderstanding.